The effects of interval- vs. continuous exercise on excess post-exercise oxygen consumption and substrate oxidation rates in subjects with type 2 diabetes - Karstoft, Kristian; Wallis, Gareth A.; Pedersen, Bente K.; Solomon, Thomas P.J. (Metabolism, clinical and experimental, 2016)
For unknown reasons, interval training often reduces body weight more than energy-expenditure matched continuous training. We compared the acute effects of time-duration and oxygen-consumption matched interval- vs. continuous exercise on excess post-exercise oxygen consumption (EPOC), substrate oxidation rates and lipid metabolism in the hours following exercise in subjects with type 2 diabetes (T2D). Following an overnight fast, ten T2D subjects (M/F: 7/3; age=60.3±2.3years; body mass index (BMI)=28.3±1.1kg/m2) completed three 60-min interventions in a counterbalanced, randomized order: 1) control (CON), 2) continuous walking (CW), 3) interval-walking (IW – repeated cycles of 3min of fast and 3min of slow walking). Indirect calorimetry was applied during each intervention and repeatedly for 30min per hour during the following 5h. A liquid mixed meal tolerance test (MMTT, 450kcal) was consumed by the subjects 45min after completion of the intervention with blood samples taken regularly. Exercise interventions were successfully matched for total oxygen consumption (CW=1641±133mL/min; IW=1634±126mL/min, P>0.05). EPOC was higher after IW (8.4±1.3l) compared to CW (3.7±1.4l, P<0.05). Lipid oxidation rates were increased during the MMTT in IW (1.03±0.12mg/kg per min) and CW (0.87±0.04mg/kg per min) compared with CON (0.73±0.04mg/kg per min, P<0.01 and P<0.05, respectively), with no difference between IW and CW. Moreover, free fatty acids and glycerol concentrations, and glycerol kinetics were increased comparably during and after IW and CW compared to CON. Interval exercise results in greater EPOC than oxygen-consumption matched continuous exercise during a post-exercise MMTT in subjects with T2D, whereas effects on substrate oxidation and lipid metabolism are comparable.